Epidemia e differenziazione territoriale (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper examines the regulatory measures taken by the Government to deal with the Sars-Cov-2 epidemic. In particular, the authors highlight how, in addition to introducing excessive restrictions on constitutional freedoms, they adopt a uniform approach, treating reasonably different territorial situations in the same way. This concerned the situation of the main islands, and in particular of the Region of Sardinia, where a different modulation of restrictions to constitutional freedoms would probably have been more appropriate depending on the different danger and other factors relevant to the decision, such as population density and socio-economic context.
Keywords: CoViD-19; pandemic emergency; principle of reasonableness; territorial differentiation; constitutional freedoms